Investigation of Teacher Candidates’ Competence Perception and Attitude towards Teaching - KAYA, Erdi (Asian Journal of Education and Training, 2019)
In this research, it was aimed to investigate the self-competence perception and attitudes towards teaching profession of teacher candidates’ who study in different universities in terms of universities. It was observed that the level of self-competence perception of the students participating in the study did not differ statistically significantly (p>0,05), and the attitude levels related to teaching profession differed statistically significantly based on the universities they studied (p<0,05). The data collected within the research were analyzed using SPSS 22 software. Mann Whitney U test was used to compare scale scores of university students participating in the study according to gender, academic success level and sports activities while Kruskal Wallis H test was used to compare scale scores according to their age groups, universities, departments and income status. According to the results of the study, it was observed that the attitudes of university students participating in the study towards teaching profession and their competence perception levels related to themselves did not differ statistically significantly according to their sports habits. Upon examination of it is observed that the level of self-competence perception of the university students participating in the study did not differ statistically significantly, and their attitude levels related to teaching profession differed statistically significantly based on their income levels. In the attitude towards teaching profession, the attitude level of students with average income levels are statistically significantly higher than the attitude level of students with higher income levels.